2008
DOI: 10.5433/1679-0359.2008v29n2p339
|View full text |Cite
|
Sign up to set email alerts
|

Composição do conteúdo de ácidos fenólicos no bagaço de maçã (Malus sp)

Abstract: The present work aimed the study of phenolic acids composition in apple pomace of Gala and Fuji cultivars. Phenolic acids were fractionated in phenolic acids, esterified and insoluble and analyzed by gas chromatography-mass spectrometry (GC-MS). Sixteen phenolic acids were identified in apple pomace samples. Total phenolic acids in apple pomace from Gala and Fuji cultivars were, in dry weight, 93.94 mg/ g and 68.38 mg/g, respectively. Content of free phenolic acids in apple pomace from Gala cultivar was 29.11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Apples, as well as many other vegetable products, represent a source of healthy compounds, such as phenols, molecules associated with antioxidant activity [38]. Chlorogenic, p-coumaric and caffeic acid, as well as quercetin, epicatechin, catechin, rutin, phlorizin are among the main phenolic compounds present in apples [39].…”
Section: Resultsmentioning
confidence: 99%
“…Apples, as well as many other vegetable products, represent a source of healthy compounds, such as phenols, molecules associated with antioxidant activity [38]. Chlorogenic, p-coumaric and caffeic acid, as well as quercetin, epicatechin, catechin, rutin, phlorizin are among the main phenolic compounds present in apples [39].…”
Section: Resultsmentioning
confidence: 99%
“…Apple by-products are known as a rich source of polyphenolic compounds (Soares et al 2008), and these compounds are able to protect LDL lipids from oxidative stress and enhance their resistance to damage happened by oxidants (Noll et al 2009). The findings of Nobakht (2013) showed that inclusion of different levels of dried lemon pulp just affected LDL concentration in blood serum of broilers (P < 0.05).…”
Section: Total Antioxidant Capacity and Blood Biochemicalmentioning
confidence: 99%
“…Polyphenolic compounds are responsible for the aroma and organoleptic properties of apples. Phenolic acids in apples are subdivided into benzoic acids and hydroxycinnamic acids [ 11 , 12 ]. Flavonoids possess a nucleus comprising two phenolic rings and oxygenated heterocycle compounds, and they can be categorized into different types, e.g., anthocyanins, flavonols, flavanols (e.g., catechins), flavones, and chalcones [ 13 ].…”
Section: Introductionmentioning
confidence: 99%